Differential Phosphorylation Provides a Switch to Control How α-Arrestin Rod1 Down-regulates Mating Pheromone Response in Saccharomyces cerevisiae. Issue 1 (1st May 2016) - Alvaro, Christopher G; Aindow, Ann; Thorner, Jeremy
Abstract: G-protein-coupled receptors (GPCRs) are integral membrane proteins that initiate stimulus-dependent activation of cognate heterotrimeric G-proteins, triggering ensuing downstream cellular responses. Tight regulation of GPCR-evoked pathways is required because prolonged stimulation can be detrimental to an organism. Ste2, a GPCR in Saccharomyces cerevisiae that mediates response of MAT a haploids to the peptide mating pheromone α-factor, is down-regulated by both constitutive and agonist-induced endocytosis. Efficient agonist-stimulated internalization of Ste2 requires its association with an adaptor protein, the α-arrestin Rod1 /Art4, which recruits the HECT-domain ubiquitin ligase Rsp5, allowing for ubiquitinylation of the C-terminal tail of the receptor and its engagement by the clathrin-dependent endocytic machinery. We previously showed that dephosphorylation of Rod1 by calcineurin (phosphoprotein phosphatase 2B) is required for optimal Rod1 function in Ste2 down-regulation. We show here that negative regulation of Rod1 by phosphorylation is mediated by two distinct stress-activated protein kinases, Snf1 /AMPK and Ypk1 /SGK1, and demonstrate both in vitro and in vivo that this phospho-regulation impedes the ability of Rod1 to promote mating pathway desensitization. These studies also revealed that, in the absence of its phosphorylation, Rod1 can promote adaptation independently of Rsp5 -mediated receptor ubiquitinylation, consistent with recent evidence that α-arrestins can contribute to cargo recognition by both clathrin-dependent and clathrin-independent mechanisms. However, in cells lacking a component (formin Bni1 ) required for clathrin-independent entry, Rod1 derivatives that are largely unphosphorylated and unable to associate with Rsp5 still promote efficient adaptation, indicating a third mechanism by which this α-arrestin promotes desensitization of the pheromone-response pathway.